Histological Changes in the Duodenum of Mice Treated with Cobalt - Gathwan, Khalid; Albir, Ahmed; Al-Saadi, Ali (Iraqi Journal of Science, 2024)
The present study was conducted using 16 adult male Swiss albino mice (weighing 40-50g). They were equally divided into four experimental groups. The first group was only given tap water as control during experimentation period (40 days). Group II, group III and group IV of mice were daily given a subcutaneous injection of cobalt as cobalt chloride (CoCl2) at a dose of 20mg, 40mg, and 60mg /Kg body weight respectively. The examination of the histological sections of the second experimental group of mice (low dose group) showed no particular changes in the columnar epithelial cells of the duodenum of mice. The examination of the histological sections of the third experimental group of mice (moderate dose group) showed abundant degenerative changes in the columnar epithelial cells of the duodenum of mice such as increased size, presence of spaces, and dark appearance of the nucleus while these changes were more abundant in the columnar epithelial cells of the duodenum of the fourth experimental group of mice (high dose group) in comparison with the third experimental group such as increased size, presence of spaces, and dark appearance of the nucleus.